Pembentukan Karakter Islami melalui Pembiasaan di Sekolah PETAMA Malaysia - Rini Yulia Citra; Yumna; Ardi Satrial (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
This study aims to analyze the Islamic character development model and the character values ​​developed through the development process at PETAMA School, Malaysia. The study employed a qualitative approach with a case study design. Data were collected through observation, interviews, documentation, and open-ended questionnaires involving teachers and students in a boarding school setting. Data were analyzed using data reduction, categorization, and thematic coding to identify the forms of development and the character values ​​formed. The results indicate that Islamic character development is implemented through daily activities, social interactions, teacher role models, discipline reinforcement through rules, rewards, and sanctions, as well as continuous monitoring and evaluation. This process contributes to the development of religious character, discipline, responsibility, and social care in students, with religious character being the most dominant value developed. In its implementation, the development process still faces several obstacles, such as lack of student discipline, the influence of social media, language barriers, and poor memorization. To address these conditions, the school provides guidance through a personal approach, counseling, monitoring of mobile phone use, and periodic evaluation. This research demonstrates that the boarding environment plays a crucial role in supporting the internalization of Islamic character values ​​through consistent and ongoing habituation